EMPOWERING COASTAL COMMUNITY BY IMPLEMENTING NATURAL RESOURCES MANAGEMENT (Case study in Southeast Sulawesi, Indonesia) - La Sara; Abdul Hamid; Safilu . (JOURNAL OF COASTAL DEVELOPMENT, 2011)
Economic crisis in 1997-1998 had brought about the emergence of problems of coastal communities in Indonesia, including those in Southeast Sulawesi. Most of the problems still have taken place at present, leading to the degradation of ecosystem services for natural resources. Development activities in various sectors done through unsustainable practices of utilization of natural resources have contributed to increased environmental degradation , which resulted in drastically decreased on fish population. Recently, the government and people are aware that integrated natural resources of coastal and marine management have to be set based on scientific approach. There have been several strategies formulated. Among them is integrated coastal zone management, but unfortunately it has been using top down approach. Hence, local community has no access to the programs. The effective implementation of empowerment should involve all stakeholders who have access to the coastal resources. The objectives of this work were to reduce gradually coastal resources degradation, to change fishermen behavior using illegal fishing, and to create new job using natural resources. This work was implemented in Lasongko Bay of Buton island. The present work is formulated to reduce social economic problems, which has strong correlation with environmental degradation. The programs were formulated by local community in several discussion forums based on identification of their natural resources. To alleviate poverty, rehabilitation of environmental degradation was done first which consisted of planting mangrove seeds along shoreline of the bay and establishing marine protected area. Another program implemented was fish and seaweed cultures to improve community income. The local community in groups took full participation and involvement in all programs implemented due to the role of religion and traditional figures and youth leaders. To achieve the objectives and goals of the programs, each group had a leader and held monthly meeting to discuss strategies for better life. All programs implemented showed better hope for the future due to active participation of local community in maintaining all programs of environment rehabilitation. Similarly, activities of improving income also showed better production.